2017
DOI: 10.1007/s00431-017-2882-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of non-tuberculous mycobacterial lymphadenitis in children: a case–control study

Abstract: M. avium is still the predominant bacteria causing NTM lymphadenitis in children of our region. Contact with hens has been the only risk factor for NTM lymphadenitis detected in the present study. What is Known: • M. avium is the predominant bacteria causing NTM lymphadenitis in children of our region. • There is no consensus on which environmental factors are associated with NTM lymphadenitis in children. What is New: • The only risk factor for NTM lymphadenitis found in the present study was regular contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… 12 These cases were compatible with the evidence that NTM lymphadenitis has mainly occurred in children, and MAC accounts for 80–90%. 13 Consequently, our patient is the first adult non-HIV case with concomitant NTM lymphadenitis and lymphoma.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“… 12 These cases were compatible with the evidence that NTM lymphadenitis has mainly occurred in children, and MAC accounts for 80–90%. 13 Consequently, our patient is the first adult non-HIV case with concomitant NTM lymphadenitis and lymphoma.…”
Section: Discussionmentioning
confidence: 86%
“…12 These cases were compatible with the evidence that NTM lymphadenitis has mainly occurred in children, and MAC accounts for 80-90%. 13 Consequently, our patient is the first adult non-HIV This patient presents with an EBV latency type III. It is typically observed in immunodeficiency-associated LPD and a part of EBV-positive diffuse large B cell lymphoma (DLBCL), not otherwise specified (NOS), which indicates the highly immunodeficient background.…”
mentioning
confidence: 91%
“…Symptoms in birds include emaciation, apathy and diarrhea, along with a distinct atrophy of the chest muscles. M. avium infection initially involves the intestine, and then spreads to the liver, spleen, bone marrow, lungs, air sacs, and gonads [77]. Later stages of the disease are characterized by the appearance of non-calcified nodules [77].…”
Section: Pathogenesis and Immunology Of Infection The Exact Pathogenesis Of Mac Infections And Their Virulence Factorsmentioning
confidence: 99%
“…M. avium infection initially involves the intestine, and then spreads to the liver, spleen, bone marrow, lungs, air sacs, and gonads [77]. Later stages of the disease are characterized by the appearance of non-calcified nodules [77]. In some cases, skin lesions can also be observed [76].…”
Section: Pathogenesis and Immunology Of Infection The Exact Pathogenesis Of Mac Infections And Their Virulence Factorsmentioning
confidence: 99%
“…These bacteria are also a frequent cause of disease in people infected with Human Immunodeficiency Virus (HIV) (Ristola et al 1999) or those receiving immunosuppressive treatment after transplantation or other systemic diseases (Tortoli 2006;Lastours de et al 2008;Tan et al 2016). A study 4 488 conducted by Garcia-Marcos et al (2017) showed a correlation between the occurrence of mycobacteriosis in children and their exposure to chickens. But NTM can also cause disease in adult immunocompetent patients (Piersimoni and Scarparo 2006;Santos et al 2014).…”
Section: Introductionmentioning
confidence: 99%